Seven Challenges in Parallel SAT Solving - Hamadi, Youssef; Wintersteiger, Christoph M. (The AI magazine, 2013)
This article provides a broad overview of the state of the parallel SAT solving field. A set of challenges to researchers is presented that, we believe, must be met to ensure the practical applicability of parallel SAT solvers in the future. All these challenges are described informally but put into perspective with related research results, and a (subjective) grading of difficulty for each of them is provided.